The role of bank branches in local credit markets: evidence from Brazil - Suplicy, Mariana Pereira (2016)
Credit is seen in Economic Literature as one of development drivers, promoting investment, smoothing consumption, allowing for risk sharing and the use of new production technologies. Our objective is to analyze if the physical presence of banks through bank branches is still relevant to develop local credit markets in Brazil. Since there are unobservable market characteristics that could drive both credit and bank entry, the relation between credit and branches may suffer from endogeneity. Therefore, the simple regression of credit on bank branches would be biased. To try to deal with this endogeneity, we employ an IO framework to model firm entry and use the estimated result as an instrument for observed bank branches. We find that estimations using expected values or predicted probabilities of bank branches show little to no effect of bank branches on credit. The same result is achieved when using a second IO model as an additional analysiss